2004
DOI: 10.1063/1.1789871
|View full text |Cite
|
Sign up to set email alerts
|

Quantum calculations of the O(3P)+H2→OH+H reaction

Abstract: Quantum scattering calculations are reported for the O(3P)+H2(v=0,1) reaction using chemically accurate potential energy surfaces of 3A' and 3A" symmetry. We present state-to-state reaction cross sections and rate coefficients as well as thermal rate coefficients for the title reaction using accurate quantum calculations. Our calculations yield reaction cross sections that are in quantitative accord with results of recent crossed molecular beam experiments. Comparisons with results obtained using the J-shiftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
60
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 35 publications
15
60
1
Order By: Relevance
“…The above argument is further supported by the fact that the ICSs obtained from recent crossed molecular beam measurements 11 are in a good agreement with the calculation results on the singlet PES 3 A′ and 3 A″. 24 Thus, for the sake of simplicity, we carried out the state-to-state dynamics calculations of the title reactions on the single-surface 3 A″ of Rogers et al 6 As indicated in ref 6, 951 geometries were used to the regular-accuracy MOLPRO calculations of the electronic energies for the lowest 3 A″ state of the title reactions. A rotating Morse spline method and a generalized London− Eyring−Polanyi−Sato (LEPS) double-polynomial method were employed to fit the results.…”
Section: Theoretical Methodssupporting
confidence: 81%
“…The above argument is further supported by the fact that the ICSs obtained from recent crossed molecular beam measurements 11 are in a good agreement with the calculation results on the singlet PES 3 A′ and 3 A″. 24 Thus, for the sake of simplicity, we carried out the state-to-state dynamics calculations of the title reactions on the single-surface 3 A″ of Rogers et al 6 As indicated in ref 6, 951 geometries were used to the regular-accuracy MOLPRO calculations of the electronic energies for the lowest 3 A″ state of the title reactions. A rotating Morse spline method and a generalized London− Eyring−Polanyi−Sato (LEPS) double-polynomial method were employed to fit the results.…”
Section: Theoretical Methodssupporting
confidence: 81%
“…We should mention here that Braunstein et al 20 and Balakrishnan 21 have reported their nonadiabatic dynamics calculations on the O͑ 3 P͒ +H 2 reaction very recently, and the agreement between these calculated total reaction cross sections and the experimental results tends to indicate the insignificance of the spin-orbit effects in this reaction. However, the present study differs apparently from the above investigations partly in that the problem of interest is not the spinorbit effects on the total reaction cross sections but on the fine-structure resolved reaction cross sections.…”
Section: Introductionmentioning
confidence: 96%
“…18 Owing to this experimental breakthrough and the availability of new ab initio PESs of chemical accuracy, 16,22 there currently is a renewed theoretical interest in the title reaction. 3,[18][19][20][21][22][23] Recently, Braunstein et al 20 reported the excitation function for O͑ 3 P͒ +H 2 ͑v =0−3, j =0͒ → OH+ H calculated with the quasiclassical trajectory ͑QCT͒ and time-dependent quantum-mechanical ͑TDQM͒ scattering methods on the PESs of Rogers et al 16 QCT reaction cross sections for H 2 ͑v Ͼ 0͒ were found to overestimate TDQM results by as much as a factor of Ϸ2 near threshold, although the agreement is gradually restored as the collision energy is increased. Using the same PESs, time-independent coupled-channel quantum scattering calculations by Balakrishnan 21 obtained cross sections in close agreement with the experiment and TDQM results.…”
Section: Introductionmentioning
confidence: 99%